A discussion on methodology for researching soviet literary space (Concluding discussion of the conference “Literary Field Under the Communist Regime: Structure, Functions, Illusio,” October 7–9, 2015. - Kelertas, Violeta (Colloquia, 2015)
A discussion on methodology for researching soviet literary space (Concluding discussion of the conference “Literary Field Under the Communist Regime: Structure, Functions, Illusio,” October 7–9, 2015. Moderated by Prof. Violeta Kelertas, with the participation of Prof. Marina Balina, Prof. Katerina Clark, Dr. Violeta Davoliūtė, Prof. Evgeny Dobrenko, Prof. Wolfgang Emmerich, Dr. Vilius Ivanauskas, Prof. Aušra Jurgutienė, Dr. Mindaugas Kvietkauskas, Dr. Dalia Satkauskytė).